Antibacterial Effectiveness of Noni (Morinda citrifolia) Leaf Extract on Tiger Prawn Larvae Infected with Vibrio parahaemolyticus: english - Burhanuddin Ihsan; Slamet Budi Prayitno; Desrina Desrina; Diah Ayuningrum (Journal of Aquaculture and Fish Health, 2026)
Disease attacks on tiger shrimp (Penaeus monodon) have developed in several pond areas, resulting in mass mortality and crop failure. One of them is vibriosis disease caused by the bacteria Vibrio parahaemolyticus. V. parahaemolyticus bacteria are one of the most virulent and prevalent pathogens against tiger shrimp cultivation and cause substantial economic losses to the aquaculture industry. This study aimed to analyze the antibacterial effectiveness of noni (Morinda citrifolia) leaf extract on shrimp larvae against V. parahaemolyticus in vivo. The research method was carried out experimentally with several stages: noni leaf extraction with maceration using 80% ethanol, phytochemical tests, and antibacterial tests through maintenance with extract immersion (control without extract, extract immersion for 1 hour, 2 hours, 4 hours, 8 hours, 16 hours, and 24 hours), bacterial enumeration, and water quality measurement. The results showed that tiger prawn larvae infected with V. parahaemolyticus bacteria experienced clinical symptoms with reddish color, passive swimming patterns, sideways movements, and very active reflex movements. The antibacterial effectiveness of noni leaf extract on tiger prawn larvae significantly affected V. parahaemolyticus bacteria. The content of compounds in noni leaf extract suppresses the mortality rate of tiger prawn larvae due to V. parahaemolyticus bacterial infection. The best dose was found in the extract soaking for 1, 2, 4, and 8 hours, with tiger prawn larval mortality up to 0% during maintenance.